The NLRP3 Inflammasome and Its Role in Sepsis Development - Danielski, Lucinéia Gainski; Giustina, Amanda Della; Bonfante, Sandra; Barichello, Tatiana; Petronilho, Fabricia (Inflammation, 2020)
The pathophysiology of sepsis is extremely complex. During this disease, the exacerbation of the inflammatory response causes oxidative stress, alterations in mitochondrial energy dynamics, and multiple organ failure. Some studies have highlighted the important role of the NLRP3 inflammasome in sepsis. This inflammasome is a macromolecular protein complex that finely regulates the activation of caspase-1 and the production and secretion of potent pro-inflammatory cytokines such as IL-1β and IL-18. In this review, we elucidate evidences to understand the connection between sepsis development and the NLRP3 inflammasome, the most widely investigated member of this class of receptor.